The Influence of Western Culture on the Behaviour of Senior High School Students - Farizi, Firdaus Irvan; Mustofa, Triono Ali (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine how foreign or (western) culture affects student behavior in everyday life in Indonesia and the efforts of the MAN 2 Klaten school in counteracting the influence of foreign cultures that have the potential to harm young students. which uses qualitative research methods with a case study approach conducted at MAN 2 Klaten. The population in this study were all students at MAN 2 Klaten, then sample selection was carried out using purposive sampling method and obtained 30 students. The data collection methods used were observation, interviews, and literature study. The data sources used were primary and secondary. Primary data was obtained from observations made for 1 month from March to April 2023 and interviews with students and teachers at MAN 2 Klaten. While secondary data is obtained from books and journals related to the research conducted. The data analysis technique used is Miles and Huberman's interactive analysis. Qualitative data analysis activities are carried out interactively and take place continuously until completion, so that the data is saturated. This analysis consists of 3 main things, namely data reduction, data presentation, and data verification. The conclusion of this research is that the positive behavior obtained from the influence of western culture is to increase student creativity and innovation, cultural exchange provides opportunities for students to advance, students are getting faster in mastering technology, and expanding student knowledge. While the negative behavior that arises is the loss of cultural values in students, a reduced sense of student nationalism, social inequality among students, and the occurrence of divisions among students, then efforts to prevent negative behavior due to the influence of western culture that can be done is to adjust to the norms that apply in Indonesia, instill a sense of love for the country, and be moderate.